Model-based investigation on the effects of spatial evenness, and size selection in thinning of Picea abies stands. Issue 3 (3rd April 2019) - Fransson, Peter; Nilsson, Urban; Lindroos, Ola; Franklin, Oskar; Brännström, Åke
ABSTRACT: Size and spatial distribution of trees are important for forest stand growth, but the extent to which it matters in thinning operations, in terms of wood production and stand economy, has rarely been documented. Here we investigate how the choice of spatial evenness and tree-size distribution of residual trees impacts wood production and stand economy. A spatially explicit individual-based growth model was used, in conjunction with empirical cost functions for harvesting and forwarding, to calculate net production and net present value for different thinning operations in Norway spruce stands in Northern Sweden. The in silico thinning operations were defined by three variables: (1) spatial evenness after thinning, (2) tree size preference for harvesting, and (3) basal area reduction. We found that thinning that increases spatial evenness increases net production and net present value by around 2.0%, compared to the worst case. When changing the spatial evenness in conjunction with size preference we could observe an improvement of the net production and net present value up to 8.0%. The magnitude of impact differed greatly between the stands (from 1.7% to 8.0%) and was highest in the stand with the lowest stem density.